Religious Symbols in Public Spaces in Brazil: Controversies and Propositions - Gabatz, Celso (International journal of public theology, 2022)
This article outlines issues pertinent to the valuation of religions in the Brazilian legal, social and cultural framework, particularly in its Catholic expression. It is a valorisation demonstrated in the form of approximations, contacts and compromises between instances of the state and the religious organizations. The hypothesis is that, within the current picture of religious diversity in its relation to secularity, the great challenge is not mainly in the presence of religion in public spaces, but in monopolies and privileges with an exclusivist character engendered by certain religious groups. The object of research in this approach is, therefore, the incidence of religious symbols present in Brazilian public spaces, their relevance and developments in the perspective of secularity, mainly for the field of sciences of religions, humanities, theology and law.